Radial sample load distribution under overload conditions: Analytical scale columns. Issue 19 (26th November 2017) - Sharma, Neil N. D.; Dennis, Gary R.; Shalliker, R. Andrew
ABSTRACT: The homogeneity of the sample load across the radial cross section of analytical scale columns was determined when operating under overload conditions. The study was performed using active flow technology columns operating in parallel segmentation mode. The outlet segmentation ratio was varied to enable different volume fractions of mobile phase, and thus sample, to elute from the peripheral and central flow regions of the column. The amount of solute exiting the peripheral and radial central exit ports was determined as a function of the flow segmentation ratio. The experimental data using an analytical scale column with dimensions, 100 × 4.6 mm, indicated that the sample load distribution was essentially uniform as a function of the column radial cross section. GRAPHICAL ABSTRACT: